Posterior reversible encephalopathy syndrome case report in an untreated, normotensive, ovarian cancer patient in the presence of paraneoplastic antibodies - Elad Barber; Rijini Nugzar; Vitaly Finkelshtein; Alexander Puzhevsky; Tally Levy (BMC Neurology, 2020)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) is a rare neurological condition with many associated risk factors. The presentation varies and consists of seizures, impaired visual acuity or visual field deficits, disorders of consciousness, headaches, confusion and focal neurological deficits. The diagnosis relies on clinical presentation and MRI findings. Treatment and prognosis are related to the underlying etiology. Case presentation We present a 58-year-old woman with ovarian cancer who developed symptoms and radiologic signs of PRES with no apparent trigger other than a sudden increase in blood pressure for the first time in her life and before any treatment has begun. Antibodies to collapsin response-mediator protein-5 (CRMP-5), a malignancy related paraneoplastic protein, were identified in her CSF. Conclusions We present a novel and intriguing association between PRES and antibodies against CRMP-5 which may highlight a new etiology for this condition.